Modern Rape-Revenge Movies and Shelley’s The Cenci - Sahar Jamshidian; Fazel Asadi Amjad (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2020)
Viewing Shelley’s The Cenci from the political upheavals of the nineteenth century would limit one’s response to the play to the issues of that century. However, this play continues to be played in the twenty first century, which makes one wonder how a modern spectator with a feminist inclination might react to the theme of rape and revenge. The Cenci shares with a number of movies flourishing with the rise of the second wave feminism during the 1970s, the theme of a female victim transformed into a hero-avenger, who takes law into her own hands and avenges herself in the face of a dysfunctional legal state. As revisions of the archetypal narratives of violation-revenge-violation, these modern movies have been praised for depicting heroines who are no longer powerless, miserable and victimized, but strong enough to avenge themselves with impunity. Though The Cenci repeats the traditional pattern of violation-revenge-violation, it focuses on the corruption and irresponsibility of the patriarchal legal system as well as its reformation, which have been neglected by both mythical narratives and modern rape-revenge movies. By reading The Cenci along with William Blake’s “Visions of the Daughters of Albion” and Shelley’s “Prometheus Unbound,” we examine how The Cenci challenges the modern rape-revenge movies and how Beatrice could have used her agency and her anger in a more effective way to fight against tyranny.